Efektifitas Kombinasi Jus Kiwi (Actinidia Deliciora) dan Rendaman Air Hangat pada Kaki terhadap Penurunan Tekanan Darah pada Penderita Hipertensi : The Effectiveness of Kiwi Juice (Actinidia deliciosa) Combined with Warm Foot Soaks in Reducing Blood Pressure Among Hypertensive Patients - Wulandari, Milasari; Suryadi, Bambang; Istiani, Hari Ghanesia (MPI Press, 2024)
Introduction: Hypertension, also known as the silent killer, often goes unnoticed by sufferers. It is characterized by a systolic blood pressure ≥ 140 mmHg and a diastolic pressure ≥ 90 mmHg. Kiwi fruit (Actinidia deliciosa) is rich in vitamin C and is highly beneficial for lowering high blood pressure. Warm foot soak therapy involves immersing the feet up to 10–15 cm above the ankles in warm water (39–40°C) for approximately 15 minutes. This method promotes vasodilation and body relaxation, which can help lower blood pressure. Objective: To determine the effectiveness of the combination of kiwi juice (Actinidia deliciosa) and warm foot soaking in reducing blood pressure among individuals with hypertension in RT 004, Pangkalan Jati Baru Village, Cinere, Depok. Method: This study employed a quantitative research method with a pre-experimental design using a one-group pretest-posttest approach. The sample was selected through non-probability sampling using purposive sampling technique, involving 20 respondents. Data were collected using an observation sheet. Results: The Wilcoxon test results comparing pre-test and post-test data showed that if the Asymp. Sig < 0.05, the hypothesis test interpretation concludes that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Conclusion: The combination of kiwi juice (Actinidia deliciosa) and warm foot soaking is effective in reducing both systolic and diastolic blood pressure in individuals with hypertension.